Oxygen radical production and thiol depletion are required for Ca(2+)-mediated endogenous endonuclease activation in apoptotic thymocytes. - Ariel Fernández; Jeffrey Kiefer; Lisa Fosdick; David J. McConkey (1995)
Glucocorticoid hormones stimulate apoptosis in thymocytes via a mechanism that involves changes in intracellular Ca2+, and exogenous Ca2+ can also directly promote the nuclear alterations of apoptosis (lamin degradation and chromatin cleavage) in isolated nuclei. Here we report that glucocorticoid treatment resulted in the production of reactive oxygen species and the depletion of reduced glutathione. Separation of apoptotic cells on Percoll gradients demonstrated that both effects selectively occurred in thymocytes undergoing apoptosis. Moreover, glucocorticoid-induced endonuclease activation was partially blocked by the antioxidant N-acetyl-L-cysteine. Although abrogation of methylprednisolone-induced Ca2+ increases using the intracellular Ca2+ buffer 1,2-bis(2-aminophenoxy)ethane-N,N,N',N'-tetraacetic acid resulted in inhibition of endonuclease activation, it failed to prevent GSH depletion. However, N-acetyl-L-cysteine almost completely blocked methylprednisolone-induced elevations in cytosolic calcium levels, indicating that oxidative stress was playing a role in the Ca2+ response. Our results support the idea that oxidative stress is a key component of the apoptotic effector pathway in thymocytes, and that it interacts, at least in part, with the Ca2+ response.